A narrative on the neurobiological roots of attachment-system functioning - Amir Izaki; Willem J. M. I. Verbeke; Pascal Vrticka; Tsachi Ein-Dor (Communications Psychology)
Abstract Attachment theory is one of the most comprehensive frameworks in social and developmental psychology. It describes how selective, enduring emotional bonds between infants and their caregivers are formed and maintained throughout life. These attachment bonds exhibit distinct characteristics that are intimately tied to fundamental aspects of mammalian life, including pregnancy, birth, lactation, and infant brain development. However, there is a lack of a cohesive biological narrative that explains the psychological forces shaping attachment behavior and the emergence and consolidation of attachment patterns at a neurobiological level. Here, we propose a theoretical narrative focusing on organized attachment patterns that systematically link the two primary purposes of the attachment behavioral system: the provision of tangible protection or support and the corresponding subjective feeling of safety or security. We aim for this detailed delineation of neurobiological circuits to foster more comprehensive and interdisciplinary future research.